Within-breath oscillometry for identifying exercise-induced bronchoconstriction in pediatric patients reporting symptoms with exercise - Barreto, Mario; Veneroni, Chiara; Caiulo, Mariaclaudia; Evangelisti, Melania; Pompilio, Pasquale Pio; Mazzuca, Maria Cristina; Raponi, Giorgia; Pagani, Jacopo; Parisi, Pasquale (Frontiers in Pediatrics, 2024)
Background Evaluating oscillometry parameters separately for the inspiratory and expiratory breath phases and their within-breath differences can help to identify exercise-induced bronchoconstriction (EIB) in pediatric outpatients disclosing exercise-induced symptoms (EIS). Aims To assess the response in impedance parameters following an exercise challenge in patients reporting EIS. Methods Sixty-eight patients reporting EIS (34 asthmatics and 34 suspected of asthma, age mean=10.8 years, range=6.0-16.0) underwent an incremental treadmill exercise test. Spirometry was performed at baseline and 1, 5-, 10-, 15-, and 20-minute post-exercise. Oscillometry was performed at baseline and at 3- and 18-minutes post-exercise. Bronchodilator response to 200 mcg albuterol was then assessed. EIB was defined as an FEV1 fall ≥10% from baseline. Expiratory and inspiratory resistance (Rrs) and reactance (Xrs), their z-score (Ducharme et al. 2022), and their mean within-breath differences (∆Rrs= Rrsexp-Rrsinsp, ∆Xrs= Xrsexp-Xrsinsp) were calculated. Receiver operating characteristic (ROC) curves and their areas (AUCs) were used to evaluate impedance parameters performances in classifying EIB. Results Asthmatic patients developed EIB more frequently than those suspected of asthma [18/34 (52.9%) vs 2/34 (5.9%), p<0.001]. In the 20 subjects with EIB, Rrsinsp, Rrsexp, Xrsinsp, and Xrsexp peaked early (3’), and remained steady except for Xrsinsp, which recovered faster afterward. ∆Xrs widened 18 minutes following the exercise and reversed sharply after bronchodilation (-1.81±1.60 vs -0.52±0.80 cmH2O*s/L, p<0.001). Cut-offs for EIB leading to the highest AUCs were a rise of 0.41 in z-score Rrsinsp (Se: 90.0%, Sp: 66.7%), and a fall of -0.64 in z-score Xrsinsp (Se: 90.0%, Sp: 75.0%). Accepting as having “positive” post-exercise oscillometry changes those subjects who had both z-scores beyond respective cut-offs, sensitivity for EIB was 90.0% (18/20) and specificity 83.3% (40/48). Conclusion Oscillometry parameters and their within-breath differences changed markedly in pediatric patients presenting EIB and were restored after the bronchodilator. Strong agreement between z-scores of inspiratory oscillometry parameters and spirometry supports their clinical utility, though larger studies are required to validate these findings in a broader population.